127k views
5 votes
If f(x)=1/2 x-6 what is the equation for f–1(x)?

A. f–1(x) = 2x + 6

B. f–1(x) = 2x – 6

C. f–1(x) = 2(x + 6)

D. f–1(x) = 2(x – 6)

User Varna
by
5.9k points

2 Answers

1 vote
I hope this helps you
If f(x)=1/2 x-6 what is the equation for f–1(x)? A. f–1(x) = 2x + 6 B. f–1(x) = 2x-example-1
User Logiraptor
by
6.0k points
6 votes

Answer:

Option C
f^(-1)(x)=2(x+6)

Explanation:

we have that


f(x)=(1)/(2)x-6

Let


y=f(x)


y=(1)/(2)x-6

Exchange the variables x for y and y for x


x=(1)/(2)y-6

Isolate the variable y


x+6=(1)/(2)y


y=2(x+6)

Let


f^(-1)(x)=y


f^(-1)(x)=2(x+6)

User Leiyc
by
6.1k points